Gentle Cesarean Birth. Issue 3 (May 2016) - Wisner, Kirsten
Abstract : What can be done during cesarean birth to promote the birth aspect of the procedure while keeping the surgical safety processes in place to protect mother and baby? Our maternity nursing expert explains this trend in care during childbirth.